x(x+1)分之1+(x+1)(x+2)分之一+(x+2)(x+3)分之一+...+(x+1998)(x+1999)分之一等于多少?
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 13:13:33
x(x+1)分之1+(x+1)(x+2)分之一+(x+2)(x+3)分之一+...+(x+1998)(x+1999)分之一等于多少?x(x+1)分之1+(x+1)(x+2)分之一+(x+2)(x+3)
x(x+1)分之1+(x+1)(x+2)分之一+(x+2)(x+3)分之一+...+(x+1998)(x+1999)分之一等于多少?
x(x+1)分之1+(x+1)(x+2)分之一+(x+2)(x+3)分之一+...+(x+1998)(x+1999)分之一等于多少?
x(x+1)分之1+(x+1)(x+2)分之一+(x+2)(x+3)分之一+...+(x+1998)(x+1999)分之一等于多少?
1/x(x+1)=1/x-1/(x+1)
1/(x+1)(x+2)=1/(x+1)-1/(x+2)
后面以此类推
原式=1/x-1/(x+1)+1/(x+1)-1/(x+2)+……+1/(x+1998)-1/(x-1999)
=1/x-1/(x-1999)
=1999/x(x-1999)
x(x+1)分之1+(x+1)(x+2)分之一+(x+2)(x+3)分之一+...+(x+1998)(x+1999)分之一
=[1/x-1/(x+1)]+[1/(x+1)-1/(x+2)]+...[1/(x+1998)-1/(x+1999)]
=1/x-1/(x+1999)
=1998/x(x+1999)
x(x+1999)分之1998
1/x-1/(x+1)+1/(x+1)-1/(x+2)+....+1/(x+1998)-1/(x+1999)
=1/x-1/(x+1999)
=1999/x(x+1999)
(x-2分之x-1)/2-x分之4x
x-1分之x²+5x - x²-x分之2x²+4x
X(X-1)分之2X+1
(x-1分之2x-x+1分之3x)除以x^2-1分之x
(x-1分之2x - x+1分之x)×x分之x²-1=
(x平方-2x分之x+2-x平方-4x+4分之x-1)乘4-x分之x
(x-2x分之x+2 - x-4x+4分之x-1)/x分之x-4
(x-(x+1分之2x))除以x^2-1分之x^2-2x+1
[x-(x+1分之2x)]÷x²-1分之x²-2x+1
x^2-x+3分之1-2x,-x^2+x-3分之2x-1
x方-2x+1分之x方-1+x-2分之x方-2x
x²-2x分之x+2-x²-4x+4分之x-1
先化简再求值 x-1分之4(x-x)+(x-2)
2x分之1- x+y分之1(2x分之x+y -x-y)化简
1-x平方-4分之4x=x+2分之x+x-2分之2
x的平方-9分之2x+3-x分之1+x+3分之x+2
(x-2分之3x-x+2分之1)乘x分之x平方-4
x²+x分之2+x²-x分之3=x平方-1分之4